2018
DOI: 10.1093/jscr/rjy296
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid method with explorative laparoscopy and anterior open approach for re-recurrent inguinal hernia

Abstract: The new guidelines of the HerniaSurge group recommend that only an expert hernia surgeon should repair a re-recurrent inguinal hernia. We report the efficacy of the hybrid method with explorative laparoscopy and anterior open approach for re-recurrent inguinal hernia repair. A 61-year-old man underwent anterior open preperitoneal mesh repair for right inguinal direct hernia and laparoscopic transabdominal preperitoneal repair for recurrence. Two years after the second surgery, re-recurrent inguinal hernia was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 4 publications
0
8
0
1
Order By: Relevance
“…Diagnostic laparoscopy can be useful for second recurrences and ≥ third recurrences to decide which surgical access route offers the best outcome prospects for repair of a re-recurrence [ 23 , 24 ]. The laparoscopy findings will make a valuable contribution when deciding whether a laparo-endoscopic procedure or an open technique assures better conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic laparoscopy can be useful for second recurrences and ≥ third recurrences to decide which surgical access route offers the best outcome prospects for repair of a re-recurrence [ 23 , 24 ]. The laparoscopy findings will make a valuable contribution when deciding whether a laparo-endoscopic procedure or an open technique assures better conditions.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 After OPMR, totally extraperitoneal repair or TAPP seems difficult because the previously placed mesh may be an obstacle during the exfoliation of the parietal peritoneum. During exfoliation, these laparoscopic procedures appear likely to cause chronic pain if the "trapezoid of disaster," 1,[3][4][5] to which the previously placed mesh was adhered, especially in TIPPMR, is injured. For these reasons, even in Europe and the United States, surgeons tend to avoid performing CLR for RIH after OPMR for fear of patients developing chronic pain.…”
Section: Introductionmentioning
confidence: 99%
“…1 As such, CLR for RIH after OPMR is not widely performed. [1][2][3][4][5] However, a meta-analysis showed that the incidence of chronic pain was similar between the open and laparoscopic approaches for RIH. Despite this, open repair for RIH is considered more likely than laparoscopic repair to cause chronic pain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, an anterior approach can be used to treat a recurrent inguinal hernia after a failed posterior approach according to the HerniaSurge Group and European Hernia Society (EHS) guidelines [7]. Sakamoto et al reported the use of a “hybrid method,” i.e., explorative laparoscopy combined with open anterior repair, for a case of re-recurrent hernia after a failed anterior and posterior approach [8]. Although we performed a similar hybrid method on a patient who underwent primary repair via the laparoscopic transabdominal preperitoneal approach (TAPP), our technique is new to recurrent indirect hernia repair.…”
Section: Introductionmentioning
confidence: 99%